Identification and validation of a novel necroptosis-related prognostic signature in cervical squamous cell carcinoma and endocervical adenocarcinoma - Zhang, Weiyu; Cao, Wujun; Tong, Zhuting; Jin, Qinqin; Jiang, Xiya; Yang, Yinting; Yao, Hui; Chen, Guo; Gao, Wei; Zhu, Yuting; Zhou, Shuguang (Frontiers in Oncology, 2022)
Background: The purpose of this study was to investigate the prognostic signature of the necroptosis-related lncRNAs (NRLs) and explore their association with immune-related functions and sensitivity of the therapeutic drug in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). Methods: The UCSC Xena provided lncRNAs sequencing and clinic data about CESC, and necroptosis gene list was from the KEGG. NRLs were selected by structuring a co-expression network of lncRNAs and necroptosis-related genes. To further screen lncRNAs, we used the univariate Cox regression method, Lasso regression and multivariate Cox regression. Afterwards the NRLs signature was established. We used the xCell algorithm and ssGSEA to clarify the pertinence between immune infiltration and NRLs expressions in CESC patients and explored relationship between the target lncRNAs and immune-related genes. By leveraging the GDSC database, therapy sensitive response of the prognostic signature was forecasted and performed the experimental validation. We performed the GSEA enrichment analysis with the aim of recognizing the potential pathway related to the individual prognostic signature. Results: The two prognostic NRLs (AC009095.1 and AC005332.4) showed significant diversity and constituted the NRLs signature. On the grounds of our signature, risk score was an independent element which was bound up with patients outcome (HR= 4.97 CI: 1.87 - 13.2, P = 0.001). The CESC patients were classified by the median risk score. Immune infiltration analysis revealed significant increases in CD4 + Tcm, Eosinophils, Epithelial cells, Fibroblasts, NKT, Plasma cells, Platelets and Smooth muscle in the high-risk group (P< 0.05). Target lncRNAs also showed some correlation with NRGs. The estimated IC50 values of Bicalutamide, CHIR.99021 and Imatinib were lower in the high-risk group. Through the subsequent experimental validation, both AC009095.1 and AC005332.4 were significantly higher expressed in SiHa than in Hela. AC009095.1 was expressed higher in SiHa than in HUCEC, but the expression of AC005332.4 was reversed. Conclusions: This study elucidated that NRLs , as a novel signature, were indispensable factors which can significantly influence the prognosis of patients with CESC and could provide novel clinical evidence to serve as a potential molecular biomarkers for future therapeutic targets.